أثر جودة الخدمة في مراكز التدريب على ممارسة جودة التدريس من خلال التنمية المهنية لدى معلمي المدارس الحكومية في سلطنة عمان - مقبالية، فاطمة صالح علي (Kulliyyah of Education, International Islamic University Malaysia, 2022)
The topic of service quality has been of great concern for educational institutions around the world, as it is considered the main introduction for developing and improving the educational systems of those institutions. This study aimed at investigating the impact of service quality in training centers on the practice of teaching quality through professional development for public school teachers in the Sultanate of Oman. The researcher has used the analytical descriptive approach for its suitability for the nature and objective of this research. The study community has included all teachers of the Sultanate of Oman in the academic years 2018 and 2019. The sample was chosen using the random cluster method and reached (382) male and female teachers. To achieve the objectives of the study, the study tool was built, which is a questionnaire of (69) items. Statistical analysis programs were used for data analysis including SPSS and Smart PLS. Descriptive data analysis has been conducted, and the results have been discussed based on the responses of the study sample. The study model has been checked using confirmatory factor analysis. The study results showed a direct effect for service quality in the training centers on the professional development of teachers in the public schools of the Sultanate of Oman.